Tumors of the Central Nervous System: An 18-Year Retrospective Review in a Tertiary Pediatric Referral Center - AGHAYAN GOLKASHANI, Hosein; HATAMI, Hossein; FARZAN, Abdonaser; MOHAMMADI, Hassan Reza; NILIPOUR, Yalda; KHODDAMI, Maliheh; JADALI, Farzaneh (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Aghayan Golkashani H, Hatami H, Farzan A, Mohammadi HR, Nilipour Y, Khoddami M, Jadali F. Tumors of the Central Nervous System: An 18-Year Retrospective Review in a Tertiary Pediatric Referral Center. Iran J Child Neurol. Summer 2015;9(3):24-33. Abstract Objective Few studies exist on the demographics and trends of pediatric central nervous system (CNS) tumors in Iran. In this study, we retrospectively reviewed all cases with confirmed CNS tumors admitted to Mofid Pediatric Hospital, Tehran, Iran during the last 18 years. Materials & Methods Data on gender, age of diagnosis, pathologic classification and tumor location were extracted from the available medical records. We used the last version of International Classification of Childhood Cancer. Result Overall, 258 (81.9%) brain tumors and 57 (18.1%) spinal tumors were identified. Our subjects comprised of 147 (46.7%) female and 168 (53.3%) male children. More male dominancy was observed in brain tumors with a male to female ratio of 1.2 compared with 1.03 of spinal tumors. Malignant CNS tumors were most common in 1-4 yr age group. The four most common brain tumors in our subjects were astrocytomas, medulloblastoma, ependymoma and craniopharyngioma. Overall, 53.1% of the brain tumors were supratentorial. Gliomas, PNET and neuroblastma were the most frequent primary spinal tumors in our study. We observed an increasing trend for both brain and spinal tumors that was more remarkable in the last 5 years. Conclusion Our results are comparable with similar single center studies on CNS tumors during childhood. The observed disparities could be attributed to the single center nature of our study and geographical, environmental and racial variations in pediatric CNS tumors. The increasing trend of both brain and spinal tumors could warrant further investigations at provincial and national levels to investigate probable contributing environmental risk factors.